Comparative study of stenting and ostium packing in Endoscopic Dacryocystorhinostomy for Primary Acquired Nasolacrimal Duct Obstruction - Chin, Joyce (Sci Rep, 2020)
In this retrospective study, we compared the efficacy and safety of mechanical adjuvants in mucosal-sparing, mechanical endoscopic dacryocystorhinostomy (MMED) for primary acquired nasolacrimal duct obstruction (PANDO). 116 adult patients (90 female) aged 61 ± 11 received one of the following after MMED without topical mitomycin: no stenting or packing (group 1, n = 25), 1-week ostium packing by ribbon gauze (group 2, n = 29) or non-medicated absorbable gelatin sponge (group 3, n = 25), 8-week bicanalicular stenting (group 4, n = 28). 104 patients(92%) provided 12-month outcomes. Number of patients, age, gender, surgeon, and osteotomy size were comparable among groups (p = 0.4–0.9). Marginal significance was found in anatomical (group 1:80%, group 2:96.6%, group 3:96%, group 4:96.4%, p = 0.05) but not functional success (group 1:85%, group 2:85.7%, group 3:83.3%, group 4:88.9%, p = 0.75) at postoperative 12-month. Patients receiving any packing or stenting achieved better anatomical (96% versus 80%, p = 0.015) but not functional success (85% versus 86%, p = 0.90) compared to those receiving none. More patients receiving stenting developed postoperative granuloma than those who did not (87% versus 63%, p = 0.04). 1-week ostium packing was found to be as effective as 8-week bicanalicular intubation in improving anatomical outcome after MMED for PANDO. Functional outcome, however, did not differ among patients receiving mechanical adjuvant or not.